2018
DOI: 10.1007/s00404-018-4847-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for gestational diabetes mellitus in twin versus singleton pregnancies

Abstract: Women with twins are at increased risk of GDM, mainly due to a higher rate of diet-treated GDM. Despite higher baseline risk of GDM in women with twins, the effect of known risk factors for GDM is similar to that observed in singletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 28 publications
5
46
3
Order By: Relevance
“…Elevated levels of UA and a higher prevalence of GDM in twin pregnancies, compared with those in their singleton counterparts, have been reported previously. 24,25 Thus, the inclusion of twin pregnancies may overestimate the relationship between GDM and the chosen markers of kidney function. Therefore, twin pregnancies were excluded from the study (n = 9).…”
Section: Patients and Methods Subjectmentioning
confidence: 99%
“…Elevated levels of UA and a higher prevalence of GDM in twin pregnancies, compared with those in their singleton counterparts, have been reported previously. 24,25 Thus, the inclusion of twin pregnancies may overestimate the relationship between GDM and the chosen markers of kidney function. Therefore, twin pregnancies were excluded from the study (n = 9).…”
Section: Patients and Methods Subjectmentioning
confidence: 99%
“…One of the main objectives of the present study was to investigate the risk factors for GDM in women with DC twin pregnancies. Advanced maternal age (>34 years) and high prepregnancy BMI (>24.9 kg/m 2 ) are the two most recognized risk factors for GDM 20,23,31 . According to our previous study of women with singleton pregnancies 23 , the rates of maternal age >34 years, GDM in women aged ≤34 years and GDM in women aged >34 years were 45%, 6% and 13%, respectively.…”
Section: Estimation Of Minimum Sample Sizementioning
confidence: 99%
“…Therefore, clinicians require not only updated, but consistent information to counsel and manage these patients. Second, prior studies were mainly carried out on American and European populations [3][4][5][6][7][8][9][10][11][12][13][14]16,17,[20][21][22] , whereas only one was on Asian women 15 . Third, our recent study showed that risk factors for GDM women with singleton pregnancies included maternal age >34 years, pre-pregnancy body mass index (BMI) >24.9 kg/m 2 , a prior history of fetal death, chronic hypertension, genetic amniocentesis and artificial reproductive technology 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 10 11 Hiersch et al recently found that the increased risk of GDM among twin pregnancies was mainly due to a higher incidence of mild, diet-treated GDM, and suggested that the mildly increased glucose intolerance may be a beneficial physiologic response to increased maternal metabolic rates and increased glucose demand for two fetuses. 12 …”
mentioning
confidence: 99%